Macrophage Infiltration and ITGB2 Expression in ESCC: A Novel Correlation - Tao Huang; Longqian Wei; Huafu Zhou; Jun Liu (Cancer Medicine)
ABSTRACT Background Esophageal squamous cell carcinoma (ESCC) is one of the most prevalent and lethal malignancies worldwide. Despite progress in immunotherapy for cancer treatment, its application and efficacy in ESCC remain limited. Therefore, there is an ongoing need to explore potential molecules and therapeutic strategies related to tumor immunity in ESCC. Methods In this study, we integrated high‐throughput sequencing data, gene chip data, single‐cell sequencing data, and various bioinformatics analysis methods along with experimental approaches to identify key genes involved in immune infiltration in ESCC and investigate their relationship with immune cell development, as well as the potential of these key genes in immunotherapy. Results We discovered and validated a positive correlation between macrophage infiltration and ITGB2 expression in ESCC. ITGB2 is overexpressed in ESCC and has potential as a prognostic biomarker for the disease. We present for the first time the finding that the expression of ITGB2 in infiltrating macrophages increases as these macrophages polarize toward a tumor‐promoting phenotype in ESCC. Moreover, during the progression of ESCC, ITGB2 expression in infiltrating macrophages is upregulated. The higher the expression of ITGB2, the more feasible it is to target macrophages. Additionally, we found that evaluating immune therapy responses in ESCC patients through ITGB2 expression is a viable approach. Furthermore, we identified three miRNAs associated with abnormal ITGB2 expression, providing insights into the upstream molecular interactions of ITGB2. Conclusions Macrophage infiltration in ESCC is closely associated with ITGB2, which holds significant potential for immunotherapy applications in ESCC. Based on our findings and prior studies, we propose a novel hypothesis: inducing M1 macrophages in vitro, knocking out ITGB2, and then reinfusing these ITGB2‐knockout M1 macrophages into ESCC patients may represent a promising new immunotherapy strategy, providing a new avenue for ESCC immunotherapy.